Minor harbours as dispersal hubs in the Mediterranean Sea: The case of non–indigenous species in an Italian port - Antonina Badalucco; Fabio Bozzeda; Fabio Crocetta; Andrea Desiderato; Cengiz Koçak; Joachim Langeneck; Emanuele Mancini; Caterina Martino; Francesco Mastrototaro; Serena Mucciolo; Luigi Musco; Maria Giovanna Parisi; et al. (Regional Studies in Marine Science, 2026)

Population structure study across the North Pacific for representatives of the deep-sea family Neotanaidae (Crustacea: Peracarida) reveals cryptic species separated by depth and geographical distance - Emma Palacios Theil; Andrea Desiderato; Serena Mucciolo; Magdalena Błażewicz (Progress in Oceanography, 2026)

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Distribution, diversity and diversification from DNA barcoding perspective: The case of Gammarus radiation in the ancient Lake Ohrid - Tomasz Mamos; Michał Grabowski; Lidia Sworobowicz; Walter Salzburger; Sasho Trajanovski; Denis Copilaş‐Ciocianu; Serena Mucciolo; Anna Wysocka (Journal of Biogeography, 2024)
Aim A detailed, comparative DNA‐barcoding and morphospecies‐based overview of the vertical and horizontal distribution of Lake Ohrid's endemic Gammarus species flock is provided. Re‐evaluation of the time frame for the onset of the species flock and identification of events that putatively influenced diversification processes. Location Lake Ohrid, Balkan Peninsula, Europe. Taxon Gammarus species flock (Amphipoda, Crustacea). Methods Extensive sampling and DNA barcoding of 600 individuals was carried out. DNA sequences were analysed using species delimitation methods, haplotype network reconstructions, Bayesian molecular dating and demographic analyses. The COI‐based species delimitation results were validated with nuclear 28S RNA data. Results The species flock distribution has a weak horizontal but clear vertical structure. The diversity along bathymetric gradients correlates with temperature and salinity; and the highest diversity is observed in sublittoral and springs on the lake's shore. Two new molecular units representing putatively new species are revealed and supported also by the nuclear marker. The onset of flock radiation overlaps with the time of lake formation. The COI gene shows signs of positive selection and an acceleration in substitution rate. The demographic changes within the flock happened during the last thousands years. Main Conclusions Distribution of the Gammarus species flock is vertically structured, reflecting habitat zonation. Parapatric speciation is one of the possible mechanisms behind the flock's diversification. Detection of new MOTUs suggests that the flock's diversity is still not fully revealed. Simultaneously, failure to collect three previously known MOTUs suggests a loss of gammarid diversity in the lake. This represents, together with the current threats to the lake ecosystem (i.e. climate changes, development of tourism), a clear call for conservation efforts. The speciation events and demographic changes within the flock relate presumably to glacial and postglacial water level changes and to the colonisation of new depth ranges and the associated springs.

New records of rarely reported species in the Mediterranean Sea (July 2023) - DANIELE GRECH; EMANUELE ASCIUTTO; RIGERS BAKIU; PIETRO BATTAGLIA; CHAIMA BEN-GRIRA; ÖZNUR YAZILAN ÇAMLIK; ROBERTO CAPPUCCINELLI; LEILA CARMONA; SAHAR CHEBAANE; FABIO CROCETTA; ANDREA DESIDERATO; FILIPPO DOMENICHETTI; et al. (Mediterranean Marine Science, 2023)
This Collective Article presents new information about the occurrence of 23 marine taxa that belong to five Phyla: two Chlorophyta, one Annelida, six Mollusca, three Arthropoda, eleven Chordata (one Ascidiacea, one Elasmobranchii and nine Teleostei) and extending from the Western Mediterranean to the Levantine Sea. All these records were reported from nine countries from the western to the eastern Mediterranean Sea, with a broad biogeographical coverage as follows: Spain: first records of the sacoglossans Cyerce graeca and Placida tardyi for the Alboran Sea and first records of the nudibranch Marionia gemmii for the Mediterranean waters of Spain; first records of nudibranch Algarvia alba in the Mediterranean Sea. Italy: First report of the long-legged crab Paragalene longicrura, a further new Mediterranean record of the rare offshore rockfish Pontinus kuhlii, first documented record of the spiny butterfly ray Gymnura altavela in Sardinia (Tyrrhenian Sea), new record of the red‐spotted wrasse Lappanella fasciata from the Messina Strait, first documented record of the rarely observed brown moray Gymnothorax unicolor in the Ionian coast, first record of the colonial ascidian Botrylloides israeliensis, first record of the Morocco dentex Dentex maroccanus, first record of mottled shore crab Pachygrapsus maurus and of an adult specimen of barracudina Lestidiops sphyrenoides in the Adriatic Sea, and further new Mediterranean records of Ross worm Sabellaria spinulosa along the same coast. Tunisia: second record of smalleye squaretail Tetragonurus cuvieri from the African Mediterranean coast. Slovenia: first records of the sea slug Trapania graeffei and Melanochlamys wildpretii, with the last one also representing the northernmost finding of this species. Croatia: northernmost record of the endangered twaite shad Alosa fallax in the Adriatic coast. Albania: first records of the Mediterranean spearfish Tetrapturus belone. Türkiye: first record from the Aegean coasts for Türkiye of the green macroalgae Cladophora battersii and Valonia aegagropila. Israel: first record of the skeleton shrimp Caprella acanthifera in the Southeastern Mediterranean Sea. Syria: first record of the Smooth grenadier Nezumia aequalis from Syrian marine waters.

Habitat use in juvenile and adult life stages of the sedentary fish Hippocampus guttulatus - Michele Gristina; Frine Cardone; Andrea Desiderato; Serena Mucciolo; Tamara Lazic; Giuseppe Corriero (Hydrobiologia, 2017)